Pengaruh Harga Terhadap Keputusan Pembelian E-Commerce Tokopedia Dimediasi oleh Brand Image pada Mahasiswa Manajemen Universitas Negeri Makassar - Andi Yusril Yasmun; Chalid Imran Musa; Muhammad Ilham Wardhana Haeruddin; Romansyah Sahabuddin; Rahmat Riwayat Abadi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine the effect of price on Tokopedia e-commerce purchasing decisions mediated by brand image on management students of Makassar State University. This study uses a quantitative method with a descriptive approach. The population of this study was 1,607 active students and the sample was taken using a non-probability sampling technique with a purposive sampling method using the slovin formula to determine the sample so that a minimum sample of 94 respondents was obtained. Data were collected through questionnaires and analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) Version 3.29 application. The research results show that (1) Price has a direct, positive and significant influence on Tokopedia e-commerce purchasing decisions, (2) Price has a direct, positive and significant influence on Tokopedia e-commerce brand image, (3) Brand image has a direct, positive and significant influence on Tokopedia e-commerce purchasing decisions, (4) Brand image partially mediates the relationship between price and Tokopedia e-commerce purchasing decisions.